2017
DOI: 10.3390/nu9101078
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogen Concentrations in Human Urine as Biomarkers for Dietary Phytoestrogen Intake in Mexican Women

Abstract: There has been substantial interest in phytoestrogens, because of their potential effect in reducing cancer and heart disease risk. Measuring concentrations of phytoestrogens in urine is an alternative method for conducting epidemiological studies. Our objective was to evaluate the urinary excretion of phytoestrogens as biomarkers for dietary phytoestrogen intake in Mexican women. Participants were 100 healthy women from 25 to 80 years of age. A food frequency questionnaire (FFQ) and a 24 h recall were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…Several studies have demonstrated that urinary phytoestrogens have also predicted one’s habitual intake of phytoestrogens and remain relatively stable in adolescents. These findings are from a longitudinal study involving urinary phytoestrogens and dietary intake over many years [50,78,79,80,81]. On the basis of these results, further studies should be pursued in an attempt to untangle phytoestrogen differences, given that each phytoestrogen may influence cognition differently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that urinary phytoestrogens have also predicted one’s habitual intake of phytoestrogens and remain relatively stable in adolescents. These findings are from a longitudinal study involving urinary phytoestrogens and dietary intake over many years [50,78,79,80,81]. On the basis of these results, further studies should be pursued in an attempt to untangle phytoestrogen differences, given that each phytoestrogen may influence cognition differently.…”
Section: Discussionmentioning
confidence: 99%
“…Quality control measures, limits of detection, and normal ranges for phytoestrogens for this study are explained elsewhere [45,46,47]. Prior studies have indicated that urinary phytoestrogens are reliable biomarkers for representing daily intake and habitual intake of isoflavones and lignans [48,49,50,51].…”
Section: Methodsmentioning
confidence: 99%
“…This Special Issue “Effects of Polyphenol-Rich Foods on Human Health” comprises 64 peer-reviewed papers, including 43 original research papers [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], one case-report [ 51 ] and 20 literature reviews [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ...…”
mentioning
confidence: 99%
“…Several contributions investigated polyphenol metabolism and transformation into bioavailable molecules and underlined the importance of the clarification of the metabolic fate of polyphenols and their bioavailability in order to fully understand the molecular forms responsible for the preventive actions of polyphenols [ 13 , 15 , 17 , 26 , 35 , 36 , 43 ].…”
mentioning
confidence: 99%
“…Biomarkers of dietary intake can be used as reference instruments in validation studies, because biomarkers of diet do not rely on reporting by subjects and the measurement errors can generally be assumed to be uncorrelated with those self-reported dietary assessment methods such as FFQ and 24-h DR [51]. In a previous study that investigated the relationship between dietary intake and urinary phytoestrogen among Mexican women, Chávez-Suárez et al [52] [25, 29-31, 33, 34, 53-56]. Moreover, the lignans value of some food groups/items in the LFFQ were adopted by applying values from similar foods due to the lack of actual lignans content in published databases; these could impact on the evaluation of the LFFQ.…”
Section: Discussionmentioning
confidence: 99%